2014
DOI: 10.1097/md.0000000000000014
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Peripheral Mycotic Aneurysms Due to Infective Endocarditis

Abstract: Peripheral mycotic aneurysms (PMAs) are a relatively rare but serious complication of infective endocarditis (IE). We conducted the current study to describe and compare the current epidemiologic, microbiologic, clinical, diagnostic, therapeutic, and prognostic characteristics of patients with symptomatic PMAs (SPMAs). A descriptive, comparative, retrospective observational study was performed in 3 tertiary hospitals, which are reference centers for cardiac surgery. From 922 definite IE episodes collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 55 publications
2
39
0
4
Order By: Relevance
“…A recent Spanish study also documented and discussed a similar preponderance of low-medium virulence microorganisms, including viridans group streptococci. 16 We begin to assess here as well the clinical impact of mycotic aneurysm, particularly as it relates to the performance of cardiac surgery. There is appropriate concern that the presence of mycotic aneurysm could affect the surgical risks of bleeding with anticoagulation during surgery, and thus affect both post-surgical neurologic outcomes and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Spanish study also documented and discussed a similar preponderance of low-medium virulence microorganisms, including viridans group streptococci. 16 We begin to assess here as well the clinical impact of mycotic aneurysm, particularly as it relates to the performance of cardiac surgery. There is appropriate concern that the presence of mycotic aneurysm could affect the surgical risks of bleeding with anticoagulation during surgery, and thus affect both post-surgical neurologic outcomes and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Jednak, jeśli wielkość tętniaka zwiększa się lub pozostaje niezmieniona, prawdopodobnie pacjent będzie wymagał interwencji. Z kolei w przypadku dużego objawowego tętniaka zaleca się leczenie neurochirurgiczne lub zabieg wewnątrznaczyniowy [272]. Wreszcie, w przypadku konieczności wczesnej operacji kardiochirurgicznej można rozważyć przedoperacyjny zabieg wewnątrznaczyniowy, w zależności od istniejących uszkodzeń mózgu, stanu hemodynamicznego pacjenta i ryzyka związa-nego z interwencją zabiegową.…”
Section: Tętniaki Zakażoneunclassified
“…Following Baddour publication in 2015, regarding an American Heart Association (AHA) statement report on infective endocarditis (IE) in adults, the most common site of mycotic aneurysms was the intracranial arteries, with an incidence of 1.5-5% of cases, and an overall mortality among those with IE of 60% [17]. Some other series have reported similar findings, with intracranial arteries being the most common site for mycotic aneurysms (especially the middle cerebral artery), with and incidence of symptomatic peripheral mycotic aneurysms of 1-5% [19].…”
Section: Epidemiologymentioning
confidence: 95%
“…González et al performed a review including 922 cases of definite infective endocarditis (IE), and reported a 2% rate of symptomatic peripheral mycotic aneurysms. In their review, 66% of mycotic aneurysms were intracranial (in the region of the middle cerebral artery) and 34% were extracranial [19].…”
Section: Epidemiologymentioning
confidence: 99%